Intelligent alarm processing - Lambert-Torres, G.; Fonseca, E. F.; Coutinho, M. P.; Rossi, R. [UNESP]; IEEE (Ieee, 2006)
This paper presents the analysis that have been carried out in the alarm system of the DCRanger EMS. The intention of this study is to present the problem of alarm processing in electric energy control centers, its various aspects and operational difficulties due to operator needs. Some tests are produced in order to identify the desirable features an alarm system should possess in order to be of effective help in the operative duty.
Keywords: alarm processing; data mining intelligent systems; power system operation; control centers